The challenges and exigencies in enforcing the Paris Agreement: from the perspective of Bangladesh - Jahan, Ramisa (Penerbit Universiti Kebangsaan Malaysia, 2024)
Over the past decades, the rapid rise in global temperatures has indicated an irreversible and irresistible shift in climate conditions. In this regard, the international community has concluded various hard law instruments amongst which the Paris Agreement has emerged as the ’ideal’ climate change treaty. Nevertheless, such initiatives have also been criticized as ineffective due to multiple reasons, for instance, the inactivity of developed nations in observing their obligations, developing nation’s lack of scientific expertise and economic means and their reliance on cooperation from developed countries; the absence of an international forum to enforce climate justice and so on. Although climate change is a universal concern, its effects and adversities primarily tend to have a devastating impact on nations with vulnerable geographical locations. In this paper, the author has highlighted the significance and urgent necessity of international cooperation; the upswing in unfavorable conditions in climate-risk countries particularly Bangladesh; and the available avenues to compel ‘inactive’ yet ‘major GHG emitting’ nations to fulfil their environmental obligations.